Hubungan Tingkat Pendidikan dengan Pengetahuan Kesehatan Reproduksi Ibu Rumah Tangga di Desa Rukoh Kecamatan Syiah Kuala Banda Aceh - Asiah Asiah (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
A research in the relationship between education level and housewives’ health reproduction knowledge had been conducted. Data was colected from 27 February to 5 March 2009 at Desa Rukoh Syiah Kuala Banda Aceh. The aim of this study is to determine the relationship between education level and housewives’ health reproduction knowledge. The population in the research was 409 housewives in the productive ages at Desa Rukoh. Purposive sampling was applied to gain 35% of sample from the population (144 housewives). Parameters of this study were knowledge, understanding, and awareness towards health reproduction. Data was gained from questionaires. Product-moment correlation was used to analyse the data. The result shows  r= 0,533 rtable = 0,159 (N=144) at 5% significant level. This value indicated that there is a relationship between education level and housewives health reproduction knowledge at desa Rukoh Syiah Kuala Banda Aceh.